THE INFLUENCE OF INFLUENCER MARKETING, CONTENT QUALITY AND SHOPEE E-COMMERCE ONLINE REVIEWS ON THE PURCHASE DECISION OF THE 3SECOND BRAND - Nursamsi, Faizal; Suharto, Akhmad; Samsuryaningrum, Ira Puspitadewi (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
Business people are required to provide better innovation, so that fashion trends always develop. In today's society, people are required to keep up with current developments in the fashion sector so that they are seen as cool and confident in their social circle. This research aims to determine and analyze the influence of Influencer Marketing, Content Quality and Shopee E-Commerce Online Reviews on Purchasing Decisions at the 3second Brand, Jember Regency. This type of research uses quantitative methods with a sample size of 90 respondents and uses non-probability sampling techniques with purposive sampling techniques, using data collection techniques in the form of questionnaires to respondents. The data analysis techniques for this research use instrument testing, classical assumptions, multiple linear regression, hypothesis testing and the coefficient of determination R2. The analysis results obtained show that influencer marketing, product quality and online reviews have a significant influence both partially and simultaneously on purchasing decisions at the 3second Brand in Jember Regency.